Analisis Lagu Aceh “Kisah Seudeh Geumpa Di Pidie Jaya” Dari Joel Keudah Menggunakan Pendekatan Mimetik - Nella Zafira (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research analyzes the lyrics of the song "Kisah Seudeh Gempa di Pidie Jaya" by Joel Keudah using a mimetic approach. This approach views literary works as dynamic representations of reality, reflecting the close relationship between works of art and real life. This song describes the tragic event of the earthquake that hit Pidie Jaya, Aceh, in 2016. Through its lyrics, this song voices the collective experience of the Acehnese people, including suffering, loss, resilience, solidarity and hope to rise again. This research uses a descriptive qualitative method, with mimetic analysis steps, such as understanding, marking and evaluating the lyrics to reveal the social and emotional values contained therein. Analysis by verse shows that this song reflects the physical, psychological, social and spiritual realities of the affected communities. The first stanza describes the chronology of the earthquake events in detail, while the second stanza expresses the emotional trauma and religiosity of the community. The third stanza highlights the physical destruction caused by the disaster, and the fourth stanza reveals the social impact in the form of the destruction of places of worship and the separation of families. The fifth and sixth stanzas convey a moral message, motivation to rise up, and spiritual introspection. The research results show that this song is not only a documentation of historical events, but also functions as a medium for cultural reflection, solidarity and empathy towards disaster victims. This song successfully describes the dynamic relationship between art, reality and human experience.